Estimating Maternal Cardiac Arrest Incidence and Outcomes: A Rare and Challenging Complication of Pregnancy That Behooves Preparedness. Issue 2 (June 2015) - Morrison, L.J.; Jeejeebhoy, F.M.
Abstract : ( Anesthesiology . 2014; 120:790–791)